Sectional measurements of shoulder muscle volume and computed tomography density in anterior shoulder instability - Keita Nagawa; Yuki Hara; Hirokazu Shimizu; Koichiro Matsuura; Kaiji Inoue; Eito Kozawa; Katsunobu Sakaguchi; Mamoru Niitsu (Scientific Reports)
Abstract In patients with anterior shoulder instability (ASI), a chronic imbalance might exist between the anterior and posterior shoulder muscles (i.e., subscapular [Ssc] vs. infraspinatus and teres minor [Isp + TM]). The balance could be evaluated as the ratio of volume (VR Ssc/Isp+TM) and computed tomography density (CT-DR Ssc/Isp+TM) using a 3D sectional approach. A total of 28 CT images (19 patients) of non-pathological shoulders (clavicular fracture [CF]) and 17 CT images (17 patients) of ASI were used. Segmentation of Ssc and Isp + TM muscles was performed; the reconstructed models were separated by the Y-view plane and the planes situated 2.5 cm and 5 cm medial to the Y-view plane to generate muscle models. VR Ssc/Isp+TM and CT-DR Ssc/Isp+TM were measured in each section of both the groups, as well as in whole muscle measurements in the CF group. VR Ssc/Isp+TM and CT-DR Ssc/Isp+TM obtained through a 3D sectional approach in the CF group were comparable to the whole muscle measurements, with a value of 1.06 for both. In the ASI group, the VR Ssc/Isp+TM was higher, whereas the CT-DR Ssc/Isp+TM was lower than those in the CF group. The VR Ssc/Isp+TM and CT-DR Ssc/Isp+TM appeared to be balanced in the CF group. However an imbalance was observed in the ASI group. Our 3D sectional measurement approach has the potential to assess the balance between the anterior and posterior shoulder muscles in ASI.